Analisis Tingkat Kepuasan Kerja Karyawan Pada CV Sumber Pangan Di Denpasar - SUPRATMAN, I WAYAN NOVA; USTRIYANA, I NYOMAN GEDE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.3, Juli 2016, 2016)
Analysis of Job Satisfaction at CV Food Sources in Denpasar Human resources is a factor of production which is very important for a company,compared with other factors of production include natural resources, capital, andskills. The purpose of this study was to determine the level of employee satisfactionCV Food Source in Denpasar. The location determination is done deliberately. Thetotal number of the population sampled that stout 40 employees CV Source of Foodin Denpasar. The factors used in this study is the satisfaction of the salary receivedby the employee, satisfaction with the social aspects in the work, satisfaction withthe attitude of the boss, satisfaction with the work environment or workingconditions, satisfaction with the award, and satisfaction with security in work ,Methods of data analysis used descriptive analysis method using a questionnaire,measured with likert scale. The results show the percentage of the level ofemployee satisfaction score of 65.96%. Achievement scores of employees CVSource Food is categorized quite satisfied, this describes the majority ofrespondents had felt quite satisfied during work in CV Source Food. It should beconsidered to improve employee job satisfaction in CV Source Food that award,salary or compensation received and the sense of safety in the work.
Keywords: employees, job satisfaction, likert scale